Impact of income and non-income shocks on child labour: Evidence from a panel survey of Tanzania - Amarakoon Bandara; Rajeev Dehejia; Shaheen Lavie Rouse (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2014)
This paper investigates the impact of income and non-income shocks on child labour using a model in which the household maximizes utility from consumption as well as human capital development of the child. Two types of shocks are considered: agricultural shocks as an income shock and the death of a parent or relatives as a non-income shock. We also investigate if access to credits and household assets act as buffers against transitory shocks. Our results indicate significant effects of crop shocks on child's overall work hours and buffering effects of access to a bank account on child labour and hunger.
Keywords: J82; J22; O13; O16; 330; child labour; buffer stocks; agricultural shocks; consumption smoothing